Transformasi Sertipikat Elektronik Dalam Perspektif Perlindungan Bagi Nasabah Kredit Perumahan Rakyat - Romadoni, Rahayu Mulia (Acten Journal Law Review, 2025)
The digital transformation in land administration through Electronic Certificates constitutes a strategic measure by the Government of Indonesia to establish a transparent and accountable land registration system. This study aims to analyze the juridical implications of Sertipikat-el regarding the legal certainty for Home Ownership Credit customers, as well as the forms of legal protection available to customers and the banking sector against the risks of digital maladministration. The research method employed is normative juridical, utilizing statutory, conceptual, and analytical approaches. The findings indicate that Sertipikat-el bolsters legal certainty by minimizing the risk of dual certification through an integrated spatial mapping system. Legal protection for customers and the banking sector is realized through cybersecurity frameworks pursuant to the Personal Data Protection Law and the principle of state responsibility regarding digital system failures. This study concludes that while digital technology enhances the efficiency of Mortgage execution, the reinforcement of regulations concerning administrative compensation for system errors is imperative to ensure equity for KPR customers as consumers of financial services.